2018
DOI: 10.1007/s11270-018-3852-8
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticle Circulation in an Aquatic Ecosystem

Abstract: Nanotechnology is a dynamically developing field of scientific and industrial interest across the entire world, and the commercialization of nanoparticles (NPs) is rapidly expanding. Incorporation of nanotechnologies into a range of manufactured goods results in increasing concern regarding the subsequent release of engineered NPs into the environment. One of the biggest threats of using NPs is the transfer and magnification of these particles in the trophic chain. The aim of the studies was the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Engineered TiO 2 nanoparticles are released into the aquatic environment from multiple point-and non-point sources. [4,85] The fate of nano-TiO 2 in the aquatic environment depends on their aggregation and sedimentation rates, transport with water and sediments and interactions with the living and non-living components of the ecosystem [85][86][87] (Figure 4). Salinity and pH (and more generally the presence of cations) as well as organic matter (including humic acids, dissolved organic matter (DOM) and particulate (POM) organic matter) may strongly affect the aggregation and sedimentation rates of nano-TiO 2 .…”
Section: The Sources and Fate Of Nano-tio 2 In The Aquatic Environmentmentioning
confidence: 99%
“…Engineered TiO 2 nanoparticles are released into the aquatic environment from multiple point-and non-point sources. [4,85] The fate of nano-TiO 2 in the aquatic environment depends on their aggregation and sedimentation rates, transport with water and sediments and interactions with the living and non-living components of the ecosystem [85][86][87] (Figure 4). Salinity and pH (and more generally the presence of cations) as well as organic matter (including humic acids, dissolved organic matter (DOM) and particulate (POM) organic matter) may strongly affect the aggregation and sedimentation rates of nano-TiO 2 .…”
Section: The Sources and Fate Of Nano-tio 2 In The Aquatic Environmentmentioning
confidence: 99%
“…It is worth noting that the PDS/O 3 /UV combination did not use solid catalysts (e.g., TiO 2 ). Recent literature reports [58][59][60] identify titanium (Ti) as a contaminant due to the drastic increase in the use of Ti in personal care products (cosmetics, sunscreens), environmental applications (photocatalysts), and drug delivery systems. Sodium persulfate (PDS) is not expected to bioaccumulate (it decomposes into ions ubiquitous in the environment) and will not be absorbed into soil or sediments due to its dissociation and high water solubility [61], whereas ozone and UV radiation are commonly used in water disinfection.…”
Section: Comparison With Other Aopsmentioning
confidence: 99%
“…For example, ROS have been detected in zebrafish embryos in vivo after their treatment with titania NPs, and smaller titania NPs causes higher ROS generation ( Figure 9 ) [ 185 ]. Moreover, Asztemborska et al [ 186 ] have found that titania NPs could be transferred from D. magna to D. rerio by dietary exposure. The estimated LC 50 of titania (particle size of 25 nm) for Japanese medaka is the same as that for D. magna , reaching 0.155 g/dm 3 .…”
Section: Toxicity Of Titanium(iv) Oxidementioning
confidence: 99%